Compiling the Physical Test Instruments for Adult Tarung Derajat Martial Arts - Ndaumanu, Gideon Elyfelet; Cloud, Hariono (Budapest International Research and Critics University, 2021)
This study aims to (1) produce a physical test instrument for combat martial arts in the adult fighting category (2) produce a manual for a physical test instrument in the adult fighting category. (3) Knowing the feasibility of the product manual for the physical test instrument for combat martial arts degrees in the adult fighting category.This research is a type of research (R&D) using a 4D development model. This development model consists of four stages, namely: (define, design, develop, disseminate). This research was conducted at PB Kodrat Yogyakarta which involved two validators, 1 material expert and 1 physical condition expert, 3 practitioners and 2 colleagues and 10 combat trainer respondents. Data collection techniques using questionnaires, methodsdelphi, and scoring rubrics. Validity testuse content validity analyzed using aikens v formula and concurrent validity analyzed using correlation product moments. Reliability test usingApha Cronbach. This study resulted in a manual product for the physical test of combat martial arts in the adult fighting category, which consisted of 12 test items, namely: (1) side splits, (2) 20 meter sprint, (3) hexagonal obstacle, (4) standing broad jump, (5) shock test (6) Expand Dynamometer (7) leg dynamometer (8) back leg dynamometer (9) push ups 1 minute, (10) sit ups 1 minute, (11) wall squat test, (12) run 2.4 km. The physical test instrument for fighting grade martial arts is declared valid with r count > from r table with details; 0.94 > 0.632 and the test was declared reliable with Cronbach's alpha value of 0.945 > 0.765. The product of the Tarung Degree physical test instrument has a feasibility percentage of 100% with a very strong/decent/ appropriate category from a material expert and 100% very strong/appropriate/feasible from a physiotherapist. The trainer's response to the manual has a percentage of 96% including in the very very strong / appropriate / appropriate category.